The Effect of Dietary Vitamin E (-Tocopherol) Level on the Lipid, Essensial Fatty Acid Level and the Hatching Rate of Catfish, Clarias batrachus Linn. - Mokoginta, I.; Syahrizal, ,; Jr., M. Zairin (Jurnal Akuakultur Indonesia, 2002)
This experiment was conducted to evaluate the dietary level of vitamin E (a-tocopherol) on the lipid, essential fatty acid level and the hatching rate of catfish, Clarias batrachus Linn. Five experimental diets with isoenergy and isonitrogen, but different vitamin E (a-tocopherol) level were used in this experiment. Dietary vitamin E levels are 18, 114, 210, 308 and 416 mg/kg diet respectively.  Fish with body weight of 18,55 a 5,11 g per fish, fed on the experimental diets at satiation, for six months.  The vitamin E, the lipid and the n-6 and n-3 fatty acid level of egg increase as the dietary vitamin E level of broodstock diet increase. However, the ratio of n-6/n-3 fatty acid of egg produced  by treatment 210 mg vitamin E/kg diet was higher than that of other treatments, which finally produced the highest hatching rate of egg (p<0,05).Key words : Vitamin E (a-tocopherol), reproduction, catfish (Clarias batrachus Linn.)